2010
DOI: 10.1002/jat.1525
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of isorhamnetin 3‐O‐neohesperidoside from Acacia salicina: protective effects toward oxidation damage and genotoxicity induced by aflatoxin B1 and nifuroxazide

Abstract: Antioxidant activity of isorhamnetin 3-O-neohesperidoside, isolated from the leaves of Acacia salicina, was determined by the ability of this compound to inhibit xanthine oxidase activity and to scavenge the free radical 2,2'-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS(.-)) diammonium salt. Antigenotoxic activity was assessed using the SOS chromotest assay. This compound has the ability to scavenge the ABTS(.+) radical by a hydrogen donating mechanism. We also envisaged the study of the antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In Addition to its antioxidant potential, the flavonol quercetin is one of the most abundant dietary flavonoids that present diverse biological properties such as antiproliferative and anticarcinogenic activities [ 17 ]. Furthermore, Bouhlel et al [ 18 ] reported that isorhamnetin 3- O -neohesperidoside was a potent inhibitor of xanthine oxidase and superoxide anion scavenger, which suggest that this flavonoid is able to protect cells against the consequences of oxidative stress. Indicaxanthin, a main betalain pigment in prickly pear fruit, is also a powerful antioxidant since it is more effective than 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox) in scavenging the 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS•+) [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Addition to its antioxidant potential, the flavonol quercetin is one of the most abundant dietary flavonoids that present diverse biological properties such as antiproliferative and anticarcinogenic activities [ 17 ]. Furthermore, Bouhlel et al [ 18 ] reported that isorhamnetin 3- O -neohesperidoside was a potent inhibitor of xanthine oxidase and superoxide anion scavenger, which suggest that this flavonoid is able to protect cells against the consequences of oxidative stress. Indicaxanthin, a main betalain pigment in prickly pear fruit, is also a powerful antioxidant since it is more effective than 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox) in scavenging the 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS•+) [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In plants, this activity is related to the presence of phenolic molecules such as flavonoids, tannins, phenolic acids, anthocyanins and others [10]. The anti-oxidant activity of phenolics is justified by the presence of conjugated double bonds, which provide resonance, and the hydroxyl groups on an aromatic ring [11], which can chelate metals, eliminate free radicals by donating hydrogen, oxidize and induce enzymes to interact and stabilize free radicals [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the effective constituents, typhaneoside and I3ON are flavonoid glycosides. Researchers have revealed the antioxidant activities of I3ON, quercetin and kaempferol in this plant (Bouhlel et al 2009(Bouhlel et al , 2010Ye et al 2012;Surapaneni & Jainu 2014), but little attention has been paid to typhaneoside. Evidence from the available literature has shown that the antioxidant activity of the flavonoids is related to the number of hydroxyl groups on the B ring, especially the 3 0 -OH and 4 0 -OH groups; this observation is attributable to the addition of hydroxyl groups to carbon atoms in the ortho position, thereby enhancing the antioxidant capacity (Lago et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The pollen of Typha angustifolia, known as Puhuang in China, contains a variety of constituents including flavonoids (Jia et al 1986;Ishida et al 1988), stigmasterols (Della Greca et al 1990), fatty acids (Gallardo-Williams et al 2002), nucleosides (Tao et al 2012) and cerebrosides (Tao et al 2010). According to the pharmacological effects of these compounds, it has been suggested that flavonoids may play a major role as an antioxidant (Bouhlel et al 2009(Bouhlel et al , 2010. Besides, the constituents in the pollen have diverse biological effects, such as analgesic activity (Ma et al 2011), inhibition of the contractile activity of isolated uterus (Su et al 2010), and protection of the human umbilical vein endothelial cells against adrenaline-induced damage (Su et al 2008).…”
Section: Introductionmentioning
confidence: 99%